Building the Centriole - Azimzadeh, Juliette (2010)
Centrioles are conserved microtubule-based organelles that lie at the core of the animal centrosome and play a crucial role in nucleating the formation of cilia and flagella in most eukaryotes. Centrioles have a complex ultrastructure with ninefold symmetry and a well-defined length. This structure is assembled from a host of proteins, including a variety of disease gene products. Over a century after the discovery of centrioles, the mechanisms underlying the assembly of these fascinating organelles, in particular the establishment of ninefold symmetry and the control of centriole length, are now starting to be uncovered.